(untitled) (International journal of artificial intelligence, 2025)
This article explores the interrelation between project management and STEM (Science, Technology, Engineering, and Mathematics) education. It highlights how project-based learning principles and management methodologies enhance students’ problem-solving skills, creativity, and teamwork within STEM disciplines. Effective project management fosters goal-oriented planning, resource allocation, and time management, which are essential competencies for both teachers and learners in STEM education. Integrating project management strategies into STEM learning not only promotes interdisciplinary collaboration but also develops students’ leadership and innovation skills necessary for real-world applications. The study emphasizes the importance of combining educational theory with practical implementation through projects to ensure sustainable and outcome-driven learning in modern education systems.